Anxiety, Practice Modification, and Economic Impact Among Iraqi Dentists During the COVID-19 Outbreak - Mahdee, Anas F.; Gul, Sarhang S.; Abdulkareem, Ali A.; Qasim, Syed Saad B. (Frontiers in Medicine, 2020)
Objectives: As health care workers on the front line during the coronavirus (COVID-19) pandemic, dental practitioners are amongst those at risk due to their close contact with potentially infected individuals. The aim of the current study was to assess the anxiety, practice modification and economic impact amongst Iraqi dentists whilst working during the outbreak. Materials and Methods: This study was performed using an online survey questionnaire with aid of Google forms from 2nd to 23rd July 2020. A total of 484 clinicians responded. The questionnaire was composed of open end, closed end, and Likert five-point scale questions to assess fear, awareness and financial impact of COVID-19 on dentists. Mann-Whitney test was used to compare two groups, whilst Kruksal-Wallis was performed by post-hoc test for multigroup comparisons. Results: The mean age of participants was 36.51±9.164 years and the majority (75.2%) of these were graduate dentists only. More than 80% of participants reported fear of catching COVID-19. The recorded fear level was higher amongst younger dentists and females. Awareness among these dentists of precautions and infection-control measures associated with COVID-19 (94%) was found to be high and to be statistically significantly affected by age, qualification and designation (except GP vs Specialist). With respect to the economic impact, about 75% of practitioners, regardless of demographical variables, reported that their income had declined by about 50%. Conclusions: The investigation provides clear insights into the anxiety, practice modifications and economic impact on dentists working in Iraq. Although there is a high level of knowledge and awareness of required practice regarding the COVID-19 outbreak among Iraqi dentists, they also reported a high level of fear which was continuously exacerbated by the rapid spread of the virus and its mortality rate. Their concern was compounded by the uncertainty as to how long this pandemic may last.